Observation analysis on characteristics of formation,evolution and transition of a long-lasting severe fog and haze episode in North China - Guo, LiJun; Guo, XueLiang; Fang, ChunGang; Zhu, ShiChao (Science China. Earth sciences, 2015)
An unusual fog and haze event lasted for one week took place during 1–7 December,2011 over North China.To investigate the characteristics and mechanism of formation,evolution,and transition of the fog and haze event,we studied the microphysical properties such as aerosol,cloud condensation nuclei（CCN）,fog droplet spectrum and liquid water content（LWC）,as well as horizontal visibility and boundary layer properties,using the data collected in the Project of Low-Visibility Weather Monitoring and Forecasting in the Beijing-Tianjin region.The results indicate that the long-lasting fog and haze event occurred in a high pressure weather system and calm wind condition.The stable boundary-layer structure resulted from temperature inversions that were built by warm advection and radiation cooling provided a favorable condition for the accumulation of polluted aerosols and the formation and development of the fog and haze event.In particular,the continuous southerly wet flow advection made the process a persistent and long-lasting event.The horizontal visibility was almost below 2 km in the whole process,and the lowest visibility was only 56 m.The average LWC was about 10^-3 g m^-3,and the maximum LWC reached 0.16 g m^-3.The aerosol number concentration was more than 10000 cm^-3,and its mass concentration ranged from 50 to 160 -g m^-3.The further study shows that the fog and haze event experienced three main processes in different intensities during the whole period,each process could be divided into three main stages：aerosol accumulation,transition and mixture of aerosol and fog,and dissipation.Each stage had different physical features：the aerosol accumulation stage was characterized by the increase of aerosol number concentration in Aitken nuclei and accumulation mode sequentially.In the transition and mixing stage of fog and haze,the latent heating produced by fog droplet condensation process and high aerosol number concentration condition intensified the Brownian coagulation process,which induced the small size of aerosols to become larger ones and enhanced the CCN activation process,thereby promoting the explosive development of the fog event.The ratio of aerosol activated to CCN reached 17%,and the ratio of CCN converted to fog droplet exceeded 100%,showing an explosively broadening of fog droplet spectrum.The decrease and dissipation of the fog was caused by an increased solar radiation heating or the passage of cold frontal system.